Determinants of Perceived Fit after Transition to Upper Secondary Education - Neuenschwander, Markus P. (Swiss Journal of Educational Research, 2018)
A high perceived stage-environment-fit does not only indicate a successful transition to vocational education and training (VET), but also predicts job satisfaction and productivity in a company. Based on the «family-school-job» research (FASE B in German), we study to what extend the perceived fit is predicted by (1) academic and social competences in primary school (competence development approach), and (2) by managerial determinants (workplace context approach). Results of stepwise regression analyses show that more perceived fit variance can be explained with the workplace approach than with the developmental approach of competence. They also indicate that students’ conflict resolution skills contribute to the workplace climate that in turn influences the development of the perceived fit.